Domniemany krąg kamienny w Pruszczu, gm. Gostycyn - Andrzejewski, Aleksander; Grabarczyk, Tadeusz (Zeszyty Wiejskie, 2014)
In 2007 the Conservation Office in Bydgoszcz commissioned archaeological research on a presumed stone circle in Pruszcz, Gostycyn Commune. This object had been capturing a great deal of interest among explorers for a long time. Preliminary examination of the construction revealed that it was an archeological object that was similar to some well known ones from the cemetery of the Wielbark culture in Odry. The features that provoked such an assumption were: similar shapes of peripheral stones, similar dimensions of the circle diameter as well as, what was discovered after exposing peripheral stones, there were some small erratic stones in their bedrock. We would also like to interpret a few erratic stones lying between the circle and the mound as highly possible marking of graves from the flat area of a potential cemetery. However, doubts started to emerge when it turned out that the peripheral stones were not connected with a wreath usually running around the circle and that there were no old lichens on the stones. In the light of our research it seems very likely that the genesis of the examined stone circle in Pruszcz is modern. The presumable builders could be either Karl Hans Konstantin von Königsmarck, the Tuchola district head or Jan Górski, the last owner of the Kamienicki land. The history of the circle seems extremely interesting and can be a significant example of the impact that archaeological discoveries have on modern architecture of landscape.